2019
DOI: 10.3390/su11247102
|View full text |Cite
|
Sign up to set email alerts
|

The Inefficiency of the Neoclassical Paradigm in the Promotion of Subjective Well-Being and Socioeconomic, and Environmental Sustainability: An Empirical Test for the Spanish Case

Abstract: The recent literature developed in the field of happiness economics highlights the overvaluation of income and material prosperity as determinants of happiness, and calls into question many of the assumptions of traditional economic theory linked to "rationality" and the "non-satiety" of the consumer. This article aimed to study which factors explain individual subjective well-being, paying special attention to the role of income and the incidence of social variables and focusing on the case of Spain. As a nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 68 publications
(96 reference statements)
0
5
0
Order By: Relevance
“…From a perspective of sustainability welfare economics, subjective wellbeing includes "life satisfaction, happiness, and a combined life satisfaction and happiness index" in the context of sustainable development [71,72]. The most material aspects are not associated with a higher level of individual subjective well-being; on the contrary, the most materialistic people are those who revealed lower levels of happiness as well as associated socioeconomic and environmental sustainability [73,74]. Sustainability and subjective well-being are also strongly interrelated domains, especially environmental aspects of sustainability, such as biodiversity conservation, with connectedness to nature being positively correlated with subjective well-being and sustainable behavior [75].…”
Section: Subjective Well-beingmentioning
confidence: 99%
“…From a perspective of sustainability welfare economics, subjective wellbeing includes "life satisfaction, happiness, and a combined life satisfaction and happiness index" in the context of sustainable development [71,72]. The most material aspects are not associated with a higher level of individual subjective well-being; on the contrary, the most materialistic people are those who revealed lower levels of happiness as well as associated socioeconomic and environmental sustainability [73,74]. Sustainability and subjective well-being are also strongly interrelated domains, especially environmental aspects of sustainability, such as biodiversity conservation, with connectedness to nature being positively correlated with subjective well-being and sustainable behavior [75].…”
Section: Subjective Well-beingmentioning
confidence: 99%
“…A recent study also found that people high in materialism sought happiness via extrinsic unsustainable sources (Lee and Ahn 2016). Conversely, Membiela-Pollàn et al (2019) suggest that rampant materialism makes people less happy.…”
Section: Happiness and Sustainability: Seminal Workmentioning
confidence: 96%
“…In cities and neighborhoods, empirical studies also suggest that self-reported happiness is related to sustainability across several indexes (Cloutier et al 2014;Souza et al 2019). On the other hand, some scholars have found higher happiness levels among people with greater environmental knowledge and concerns (Ferrer-i-Carbonell and Gowdy 2007;Membiela-Pollàn et al 2019). Supporting this premise, Cloutier and Pfeiffer (2015) have theorized a framework about the sustainability-happiness nexus.…”
Section: Happiness and Sustainability: Seminal Workmentioning
confidence: 97%
“…In recent years, several studies have further explored the link between subjective well-being and social, economic and environmental sustainability, and there is an increasing interest in exploring the relationship between sustainability and quality of life [19][20][21][22][23][24][25]. For instance, Musa et al [25] designed a new instrument aimed to measure community well-being that fully integrated ecological, economic and social sustainability and found a significant relationship between the level of well-being and sustainable urban development, especially focusing on social sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Musa et al [25] designed a new instrument aimed to measure community well-being that fully integrated ecological, economic and social sustainability and found a significant relationship between the level of well-being and sustainable urban development, especially focusing on social sustainability. Findings from a recent study carried out in Spain suggest that excess of concern for material and economic pursuit is associated with lower levels of happiness and well-being and undermines social sustainability [19].…”
Section: Introductionmentioning
confidence: 99%